Translating precision medicine for autism spectrum disorder: A pressing need. Issue 3 (March 2023) - Pérez-Cano, Laura; Azidane Chenlo, Sara; Sabido-Vera, Rubén; Sirci, Francesco; Durham, Lynn; Guney, Emre
Abstract : Autism spectrum disorder (ASD) is a heterogenous group of neurodevelopmental disorders (NDDs) with a high unmet medical need. Currently, ASD is diagnosed according to behavior-based criteria that overlook clinical and genomic heterogeneity, thus repeatedly resulting in failed clinical trials. Here, we summarize the scientific evidence pointing to the pressing need to create a precision medicine framework for ASD and other NDDs. We discuss the role of omics and systems biology to characterize more homogeneous disease subtypes with different underlying pathophysiological mechanisms and to determine corresponding tailored treatments. Finally, we provide recent initiatives towards tackling the complexity in NDDs for precision medicine and cost-effective drug discovery.